A warning by press release that the retrospective application of legislation to completed transactions will be applied: A case analysis of the Pienaar Brothers (Pty) Ltd v Commissioner of the South African Revenue Services and Another (2017) - Parker, Mashooma (Department of Commercial Law, 2020)
Pienaar Brothers (Pty) Ltd was an amalgamated company who sought to introduce a BEE element of ownership into its company in a tax efficient manner. Upon consulting their legal experts they were advised that the best manner in which they could achieve this objective was to enter into an amalgamation agreement in terms of section 44 of the ITA. At this particular time, the law was structured in a way in which it was possible to achieve this objective in a tax efficient matter, particularly because any distribution made by parties to the amalgamation transaction would be tax free. The problem however was that the tax collecting agency never intended the section 44 of the ITA amalgamation process to be STC free, and instead intended a temporary deferral thereof. To address this, the taxing authorities accordingly started putting mechanisms in place to limit the loss of such STC. On the 10 January 2007, SARS issued a public announcement stating that they planned to investigate certain corporate entities which had elaborate corporate structures that led to an impermissible loss of tax. On the 21 February 2007, the Minister of Finance stated that section 44 of the ITA, as it stood, allowed for a loss of STC as opposed to a deferral thereof, and that the taxing authorities intended on withdrawing such STC exemption in order to align it with their initial intention, and to further make such amendment retrospective to the date of such announcement. This was then once again cemented in the form of a press release on the part of SARS on that same day. Thereafter, this proposed amendment was submitted to Parliament in the Draft Taxation Laws Amendment Bill on 27 February 2007, and in May 2007, the Taxpayer completed its amalgamation transaction and achieved its BEE objective into its ownership. On the 7th June 2007 the Taxation Laws Amendment Bill was published together with an Explanatory memorandum which however no longer proposed the withdrawal of the STC exemption contained in section 44 of the ITA, but instead introduced a new addition into section 44 of the ITA. This provision now targeted a resultant company’s equity share capital and share premium, instead of the distribution of company income at the amalgamated company’s level. This new insertion was then promulgated into law on 8 August 2007 as section 44(9A) of the ITA. In complete difference to the initial proposal contained in the forewarning, the practical consequence of section 44(9A) of the ITA was that the income which rolled over from the amalgamated company to the Taxpayer (the resultant company) had in the process changed its nature from revenue to capital which was caught up in the share premium account of the Taxpayer. Section 44(9A) of the ITA accordingly targeted any distribution made by the resultant company of this share premium. The Taxpayer’s problem in the present matter arose in 2011 when SARS sought to tax the Taxpayer on its May 2007 completed transaction, particularly its distribution of its share premium at the time. In addition to this assessment, SARS furthermore also levied interest on such outstanding STC payment from 8 August 2007, the date on which the final enactment was promulgated into law. This was that which accordingly prompted the Taxpayer to bring its matter before the High Court. Here, the prime relief sought by the Taxpayer was an order of constitutional invalidity, while the second order, couched as an alternative to the first was an interpretational argument which had the effect that section 44(9A) of the ITA did not apply to Taxpayer’s distribution when it was made because it was a completed transaction. The gist of the Taxpayer’s constitutional issue requested of the court to declare that the provision did not pass constitutional muster to the extent of its retrospectivity. The court however dismissed the Taxpayer’s claims and held in favour of SARS. The paper seeks to analyse this case alongside the values of legal certainty, as espoused in the Rule of Law, and to consider the probability of success on the part of the Taxpayer if they opted to take the matter on appeal.